Patent protection, market uncertainty, and R&D investment - Dirk Czarnitzki; Andrew A. Toole (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
The real options investment theory shows that greater uncertainty about market revenues reduces current R&D investment by increasing the value of waiting. This paper presents empirical evidence that patent protection mitigates the effect market uncertainty on R&D investment.
More recent version: http://hdl.handle.net/10419/24705
Keywords: O33; O31; C25; 330; Real Options Theory; Uncertainty; R&D; Intellectual Property Protection; Censored Regression